Surface ligand controls silver ion release of nanosilver and its antibacterial activity against Escherichia coli - Long Y (Dove Medical Press, 2017)
Yan-Min Long,1,2 Li-Gang Hu,1,3 Xue-Ting Yan,1,3 Xing-Chen Zhao,1,3 Qun-Fang Zhou,1,3 Yong Cai,2,4 Gui-Bin Jiang1,3 1State Key Laboratory of Environmental Chemistry and Ecotoxicology, Research Center for Eco-Environmental Sciences, Beijing, China; 2Institute of Environment and Health, Jianghan University, Wuhan, Hubei, China; 3College of Resources and Environment, University of Chinese Academy of Sciences, Beijing, China; 4Department of Chemistry and Biochemistry, Southeast Environmental Research Center, Florida International University, Miami, FL, USA Abstract: Understanding the mechanism of nanosilver-dependent antibacterial activity against microorganisms helps optimize the design and usage of the related nanomaterials. In this study, we prepared four kinds of 10 nm-sized silver nanoparticles (AgNPs) with dictated surface chemistry by capping different ligands, including citrate, mercaptopropionic acid, mercaptohexanoic acid, and mercaptopropionic sulfonic acid. Their surface-dependent chemistry and antibacterial activities were investigated. Owing to the weak bond to surface Ag, short carbon chain, and low silver ion attraction, citrate-coated AgNPs caused the highest silver ion release and the strongest antibacterial activity against Escherichia coli, when compared to the other tested AgNPs. The study on the underlying antibacterial mechanisms indicated that cellular membrane uptake of Ag, NAD+/NADH ratio increase, and intracellular reactive oxygen species (ROS) generation were significantly induced in both AgNP and silver ion exposure groups. The released silver ions from AgNPs inside cells through a Trojan-horse-type mechanism were suggested to interact with respiratory chain proteins on the membrane, interrupt intracellular O2 reduction, and induce ROS production. The further oxidative damages of lipid peroxidation and membrane breakdown caused the lethal effect on E. coli. Altogether, this study demonstrated that AgNPs exerted antibacterial activity through the release of silver ions and the subsequent induction of intracellular ROS generation by interacting with the cell membrane. The findings are helpful in guiding the controllable synthesis through the regulation of surface coating for medical care purpose. Keywords: silver nanoparticles, surface chemistry, silver ion release, Trojan-horse-type mechanism, respiratory chain, oxidative stress